PENERAPAN STRATEGI SEGMENTASI, TARGETING, DAN POSITIONING (STP) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CAFÉ LAMANDA SUNGAI PENUH - Ayu Lestari, Anggia; Liantifa, Melifia; Abdallah, Zachari (STIE Mahardhika, 2026)
Increasingly fierce business competition requires businesses to implement appropriate marketing strategies to attract and retain consumers. One important strategy in marketing is Segmentation, Targeting, and Positioning (STP). This study aims to analyze the application of STP strategies on consumer purchasing decisions at Café Lamanda Sungai Penuh. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to consumers who had purchased products, then analyzed using descriptive and inferential statistical analysis. The results show that segmentation, targeting, and positioning strategies have a positive and significant effect on consumer purchasing decisions. Among the three variables, positioning has the most dominant influence in shaping consumer perceptions and preferences. These findings indicate that the application of the right STP strategy can increase marketing effectiveness and encourage consumer purchasing decisions. Therefore, business actors are advised to understand market characteristics, determine the appropriate target consumers, and build a strong product image in order to be able to compete sustainably.